Ovarian Cavernous Hemangioma Presenting as an Left Adnexal Mass with Elevated Ca-125: A Case Report - Nilüfer Onak Kandemir; Tulu Emre Ekem; Aykut Barut; Gamze Yurdakan; Arzu Sönmez; Şükrü Oğuz Özdamar (Medical Network, 2008)
Hemangiomas are benign vascular tumors that are rarely found in the ovaries. Ovarian hemangiomas are usually discovered incidentally at operation or autopsy. Sometimes, they present with abdominal mass and/or pain, acute abdomen, ascites or elevated CA-125 levels, simulating ovarian neoplasm. Hemangioma should be considered in the differential diagnosis of hemorrhagic ovarian lesions grossly, and proliferations of dilated blood vessels frequently seen in the hilar region of the ovary, lymphangioma, teratoma with a prominent vascular component and angiosarcoma microscopically. The treatment of choice is oophorectomy or adnexectomy, which results in a complete cure. We report a case of very rare tumor of the ovary with an unusual presentation; an ovarian cavernous hemangioma with elevated serum CA-125 levels and uterine leiomyoma.